2016
DOI: 10.1007/s13318-016-0340-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Tissue Disposition of Nanosystem-Entrapped Betulin After Endotracheal Administration to Rats

Abstract: Entrapment of betulin in nanosystem form shows promise as a novel strategy in the treatment of pulmonary diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
0
14
1
2
Order By: Relevance
“…The pharmacokinetic calculations for fucoidan in organs and plasma were performed with the Excel add-in program PK Solver. The parameters were calculated from the concentration-time data using a noncompartmental pharmacokinetic model as described previously [ 43 ]. The results are expressed as the mean ± standard deviation ( n = 5 for each time point).…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacokinetic calculations for fucoidan in organs and plasma were performed with the Excel add-in program PK Solver. The parameters were calculated from the concentration-time data using a noncompartmental pharmacokinetic model as described previously [ 43 ]. The results are expressed as the mean ± standard deviation ( n = 5 for each time point).…”
Section: Methodsmentioning
confidence: 99%
“…Noteworthy, BET exerted a pro-osteogenic effect at the low, non-toxic concentrations. Given the satisfactory bioavailability of BET at the diverse routes of administration [64,65], we can conclude that this compound has the potential to be used as a medicine or supplement in treatment of bone osteoporotic lesions, especially since the recent studies [38] indicated the anti-osteoclastic activity of BET. However, further in vivo studies in animal models are necessary to confirm the potential of BET to enhance osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, betulin and its derivatives have a broad spectrum of biological relevance, thus they have a high potential for application in transdermal systems [ 19 , 20 ]. To date, several formulations containing betulin and its derivatives have been developed [ 21 , 22 , 23 , 24 , 25 ]. However, there are no literature reports describing the penetration of vehicles containing these compounds through the skin.…”
Section: Introductionmentioning
confidence: 99%